CORRELATION BETWEEN SAVINGS AND SALARY OF EMPLOYEES IN MYSURU - Chengappa, Reshma (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Savings is an important variable for every country to be studied for the economic growth and development of any country. Savings is an important macroeconomic variable to be studied under the purview of the economic arena on an individual as well as household basis. Aggregate savings in any economy depend on a number of determinants. This study identified factors like correlation between salary per month and savings per month is 75%; difference between Indian gross savings rate and the savings in Mysuru is statistically significant; influence of assets of employees on their savings is positive; there is a positive correlation between one unit changes in salary of employees causing changes in savings and the influence of the type of the family on their savings is favourable with nuclear family. Besides, whether there is a significant difference among the reasons to save in organized sector and unorganized sectors by the employees in Mysuru is analysed.